STUDI TENTANG SOCIAL MEDIA MARKETING dan BRAND AWARENESS,WORD OF MOUTH TERHADAP MINAT BELI PRODUK MOMMILK(Studi pada pengguna Instagram,mahasiswa Universitas Diponegoro) - Fadhila, Nida; Soesanto, Harry (Faculty of Economics and Business Diponegoro University, 2016)
The purpose of this research is to prove the influence of social media marketing especially Instagram users towards the formation Word Of Mouth and Brand awareness,and also relationship between Brand awareness and word of mouth to create Intention to buy.non-probability sampling is used for sample taking and data were collected from 120 respondent which were selected using criteria of judgment that should have university students uses social media instagram and knows account instagram @ mommilk _ semarang. This research using Structural Equation Model and the method of analysis the maximum likelihood with program amos 2.0The result found that social media marketing influence positively on brand awareness and word of mouth. social media marketing most influential against word of mouth ,and also both word of mouth brand awareness do influence positively to formation of intention to buy.